2007
DOI: 10.1529/biophysj.106.099481
|View full text |Cite
|
Sign up to set email alerts
|

Dwell-Time Distribution Analysis of Polyprotein Unfolding Using Force-Clamp Spectroscopy

Abstract: Using the recently developed single molecule force-clamp technique we quantitatively measure the kinetics of conformational changes of polyprotein molecules at a constant force. In response to an applied force of 110 pN, we measure the dwell times of 1647 unfolding events of individual ubiquitin modules within each protein chain. We then establish a rigorous method for analyzing force-clamp data using order statistics. This allows us to test the success of a history-independent, two-state model in describing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 29 publications
2
68
0
Order By: Relevance
“…The probability of picking up and unfolding shorter length polyprotein constructs is significantly larger than that of picking up and unfolding full length constructs, and it is in agreement with data collected using I27 polyprotein constructs using two types of cantilevers, namely glass and gold substrates, and using constructs with or without a terminal cysteine residue [61]. The effect of the variation in probability of picking up and unfolding different numbers of domains has also been observed in the analysis of single-molecule force spectroscopy data from force-clamp spectroscopic techniques [31,55]. Experiments using a polyprotein containing 12 domains observed an unequal unfolding probability and measured that the population of observed events decreased by 22% for each extra observed unfolding event [55].…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The probability of picking up and unfolding shorter length polyprotein constructs is significantly larger than that of picking up and unfolding full length constructs, and it is in agreement with data collected using I27 polyprotein constructs using two types of cantilevers, namely glass and gold substrates, and using constructs with or without a terminal cysteine residue [61]. The effect of the variation in probability of picking up and unfolding different numbers of domains has also been observed in the analysis of single-molecule force spectroscopy data from force-clamp spectroscopic techniques [31,55]. Experiments using a polyprotein containing 12 domains observed an unequal unfolding probability and measured that the population of observed events decreased by 22% for each extra observed unfolding event [55].…”
Section: Resultssupporting
confidence: 83%
“…A previous study using single-molecule force-clamp spectroscopy measured the kinetics of protein unfolding at a constant force and found that while the majority of the experimental data could be described by a single unfolding rate constant, the remainder could not, suggesting alternative unfolding barriers in the energy landscape of the protein [31]. Another single-molecule study examined the energy fluctuations in the unfolding energy landscape of a protein and a broad distribution of unfolding rates, implying large fluctuations in the energies of the folded protein [62].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At each force, P(t u ) was fitted with a single exponential curve (dashed lines) according to the two-state model for protein unfolding. Although force-clamp experiments on an extensive pool of unfolding data have revealed deviations from twostate kinetics in ubiquitin (35,37), the single exponential fit gives rise to a reasonable first approximation of the rate of unfolding at each particular force (39). The significant effect of temperature on the mechanical stability of ubiquitin is demonstrated in Fig.…”
Section: Resultsmentioning
confidence: 93%
“…As pointed out by Brujic et al, 6 the probability that n domains in an N domain chain will be unfolded is related to the unfolding probability for an isolated domain by the binomial distribution PðN; n; tÞ ¼ N! n!ðN À nÞ!…”
Section: Michaelis-menten Model Of Enzyme Catalyzed Unfolding Of a Mumentioning
confidence: 96%